Anaerobic digestion: Technology for biogas production as a source of renewable energy—A review. Issue 2 (March 2021) - Obileke, KeChrist; Nwokolo, Nwabunwanne; Makaka, Golden; Mukumba, Patrick; Onyeaka, Helen
The authors reviewed the future prospects and previous studies on anaerobic digestion technology for biogas production and highlight the solutions to problems relating to construction and maintenance of biogas digesters, which can now be accessed in a single paper. It is the aim of the review to provide insight into the use, process and application of anaerobic digestion as an appropriate technology for biogas production from peer reviewed literature. Recent studies have shown that the microbial communities and metabolic pathways involves in anaerobic digestion are influenced by temperature. Their metabolic activities increase significantly with increase in temperature. Therefore, the findings of the review reveal that temperature is a major parameter for biogas production due to its influence on metabolic activities involved in anaerobic digestion. Hence, there is the need for insulation as well as external heating to maintain temperature stability and to avoid temperature fluctuations. More also, the anaerobic digestion technology for production of biogas is a viable option that can supplement as well as reduce the usage of non-renewable energy sources such as fossil fuel. The detailed information addressed in this study would increase biogas energy mix as well as mitigating climate change. Therefore, the study recommends the use of biogas as a clean energy for the purpose of power generation, cooking and heating.